Analisis Strategi Pemasaran KFC dan McDonald’s pada Masa Boikot Menggunakan Teori Permainan: Studi Kasus Mahasiswa Universitas Mataram - Ubaidillah, Moch Rafi Zarkasy; Febrilia, Baiq Rika Ayu; Wardhana, I Gede Adhitya Wisnu (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The impact of boycotts against global brands has directly influenced the marketing approaches of fast-food companies such as KFC and McDonald’s. This study aims to identify the most effective marketing strategies that both companies can adopt in response to these challenges. The research utilizes a two-player game theory model with a mixed strategy approach, analyzed through matrix algebra—specifically involving calculations of cofactors, adjoints, and determinants. Data were collected via questionnaires distributed to 100 students at the University of Mataram, focusing on four key strategic variables: communication, promotion, innovation, and service. The response matrices were simplified using row and column dominance elimination before further analysis. The results show that KFC’s optimal strategy consists of a combination of 60% innovation and 40% promotion. In contrast, McDonald’s performs best with a balanced strategy, applying 50% promotion and 50% innovation. A game value of –12 indicates that McDonald’s holds a relative advantage in minimizing potential losses during the boycott period. This study contributes valuable insights into quantitative marketing strategy analysis using a mathematical framework.